2022
DOI: 10.1038/s41598-022-20950-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of thermoplastic polyurethane and gelatin blended nanofibers covered stent graft in the porcine iliac artery

Abstract: Stent-grafts composed of expanded polytetrafluoroethylene (e-PTFE), polyethylene terephthalate (PET) and polyurethane (PU) are characterized by poor endothelialization, high modulus, and low compliance, leading to thrombosis and intimal hyperplasia. A composite synthetic/natural matrix is considered a promising alternative to conventional synthetic stent-grafts. This study aimed to investigate the efficacy of thermoplastic polyurethane (TPU) and gelatin (GL) blended nanofibers (NFs) covered stent-graft in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The scaffolds produced from such blends possessed novel properties such as increased stiffness, and hemo- or biocompatibility [ 21 , 22 ]. Mixtures of PU and gelatin have higher bio- and hemocompatibility, as previously demonstrated [ 23 , 24 , 25 ] and confirmed in an independent study by our Korean colleagues [ 26 ]. Thus, materials obtained from PU-gelatin blends are promising scaffolds for tissue engineering.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The scaffolds produced from such blends possessed novel properties such as increased stiffness, and hemo- or biocompatibility [ 21 , 22 ]. Mixtures of PU and gelatin have higher bio- and hemocompatibility, as previously demonstrated [ 23 , 24 , 25 ] and confirmed in an independent study by our Korean colleagues [ 26 ]. Thus, materials obtained from PU-gelatin blends are promising scaffolds for tissue engineering.…”
Section: Introductionsupporting
confidence: 82%
“…Previously, we have shown that the scaffolds of this composition demonstrate advantages over other blends of PU with gelatin (5, 10, and 20%) in terms of their biocompatibility and mechanical properties in experiments in vitro [ 24 ]. Data from the independent study showed that scaffolds obtained from a blend containing 3% Tecoflex EG-80A and 15% gelatin could be recommended as a promising material for the production of cardiovascular devices [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we developed the closed-cell SEMS using the hand-knitted technique and expanded-polytetrafluoroethylene (e-PTFE) as a covering membrane to evaluate patency, thrombosis, and degree of neointimal hyperplasia formation. The stent materials adopted in this study, nitinol, and e-PTFE, have been used extensively in stent-grafts showing good biocompatibility for the treatment of various vascular diseases 14 . Hence, the purpose of this study was to investigate the efficacy of closed-cell SEMS with or without an e-PTFE membrane in a porcine iliac artery model.…”
Section: Introductionmentioning
confidence: 99%